An Industrial systems design study on The Food People Inc. - Buenviaje, Arlene; Lamorena, Grace; Masilungan, Juvilyn; Tongco, Serafin II. (Diliman, Quezon City College of Engineering, 2006)
The study involves the Industrial Systems Analysis and Design of The Food People, inc., the maker of Fruits in Ice Cream Products. The study objectively documents the company's production operations and administrative functions as well as analyzes the company's status and performance through the use of IE tools. The study's scope involves the entire production line of TFPI and is based on production & financial data from 2002-2003. However, the study period is limited to 5 years with year 2004 as year 1. Gathering of Data was primarily based on company documents provided by TFPI, personnel interviews, plant visits and integrated audits. A SWOT Analyses was generated s based on the company's mission & vision statement. Strategy Analysis was also performed to identify the actions that TFPI plans in response to and in anticipation of changes in its external environment, its customers, and its competitors. TFPI's functional strategy relies on its very meticulous quality assurance process, the business marketing strategy relies heavily on product differentiation while the corporate strategy is looking into employing different types of expansion strategies. Verification of the identified strategies was employed before directly jumping into Problem Analysis. The policies were tested against whether or not they can be sustained in the company's external environment. Results showed an increasing trend in the demand for FIC, thus the external environment can sustain all the planned strategies of the company. Financial Analysis was also employed to identify immediate concerns of the company. Several ratios were computed to help analyze the financial position of the company, all in line with the company's strategies. A Pareto Chart of the company cast was also prepared to identify the most significant component that must be analyzed, which was identified to be the Cost of Goods Sold. Greater efficiency in the production line and scheduling will result in a reduction of the cost of goods sold, which will in turn increase the net income of the company. The Recommendations were all based on the careful analysis of areas that must be improved to ensure that the company sustains maximum profitability in pursuing their goals. The recommendations are two-fold starting with the corporate strategy recommendation and coupled by a functional study recommendation. The foremost corporate strategy recommendation involves capacity planning and the changing of the production schedule into longer work shifts for shorter work weeks. After the design of the new production schedule, the new capacity was then utilized to design the new inventory management control system. The functional business strategy recommendation proposes Production Monitoring and Control. An exhaustive Implementation plan was developed. In support of the recommendations made, a "Cost versus Cost Savings Table" of implementing the whole recommendation program was also constructed. Areas for further study were recommended to decide whether the additional aging tanks are actually necessary for operations and to develop manuals regarding the maintenance, operation, and repair of equipment for reference.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: The Food People Inc; Dairy products industry; Ice cream, ices, etc; Creameries; System design